2017
DOI: 10.1002/cbdv.201700382
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity of Essential Oils of Five Apiaceae Taxa and Some of Their Main Constituents Against Culex quinquefasciatus

Abstract: Apiaceae are aromatic herbs producing essential oils which are used on an industrial scale for various purposes. Notably, Apiaceae essential oils may replace synthetic insecticides keeping most of their efficacy and avoiding environmental pollution and human poisoning. In the present work, we explored the insecticidal potential of the essential oils from five Apiaceae taxa, namely Sison amomum, Echinophora spinosa, Heracleum sphondylium subsp. sphondylium, Heracleum sphondylium subsp. ternatum, and Trachyspemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…It has also been reported that the effect of thymol may be enhanced by the presence of pcymene (Burt 2004). However, it is surprising that this kind of oil did not produce relevant toxicity on C. quinquefasciatus and M. domestica, as previously seen for other oils with similar chemical profile or for the pure compound itself Pavela et al 2018b). Thus, we can assume that the other constituents may antagonize the mosquitocidal effects of thymol.…”
Section: Insecticidal Activitysupporting
confidence: 56%
“…It has also been reported that the effect of thymol may be enhanced by the presence of pcymene (Burt 2004). However, it is surprising that this kind of oil did not produce relevant toxicity on C. quinquefasciatus and M. domestica, as previously seen for other oils with similar chemical profile or for the pure compound itself Pavela et al 2018b). Thus, we can assume that the other constituents may antagonize the mosquitocidal effects of thymol.…”
Section: Insecticidal Activitysupporting
confidence: 56%
“…EOs repellence [ 17 , 18 ], larvicidal [ 19 , 20 , 21 ], and insecticidal activities are proven on different arthropod pests of economic importance [ 22 , 23 , 24 , 25 ]. Among them, the EOs’ efficacy has also been investigated on some Lepidoptera.…”
Section: Introductionmentioning
confidence: 99%
“…Monoterpenes such as thymol and carvacrol show LD 50 values of 25 and 43 ÎŒg·larvae −1 , respectively, when tested on early four-instar Spodoptera litura and the LD 50 of these monoterpenes increases with the larval development [ 16 ]. The toxicity of these monoterpenes is higher versus Spodoptera littoralis, Plutella xylostella , Callosobruchus maculatus and Culex quinquefasciatus , with LD 50 values as low as 0.22 ÎŒg·larvae −1 [ 17 , 18 , 19 , 20 , 21 ], whereas thymol and carvacrol toxicity versus Sitophilus granarius is lower, with LD 50 above 100 ÎŒg·larvae −1 [ 22 , 23 ]. Toxic synergistic effects of thymol and carvacrol with other monoterpenes have been also described [ 24 ].…”
Section: Introductionmentioning
confidence: 99%